Consistency of new CDF-II W boson mass with 123-model - B. Ait Ouazghour; R. Benbrik; E. Ghourmin; M. Ouchemhou; L. Rahili (Physics Letters B, 2023)
Following the recent update measurement of the W boson mass performed by the CDF-II experiment at Fermilab which indicates 7σ deviation from the SM prediction. As a consequence, the open question is whether there are extensions of the SM that can carry such a remarkable deviation or what phenomenological repercussions this has. In this paper, we investigate what the theoretical constraints reveal about the 123-model. Also, we study the consistency of a CDF W boson mass measurement with the 123-model expectations, taking into account theoretical and experimental constraints. Both fit results of S and T parameters before and after mWCDF measurement are, moreover, considered in this study. Under these conditions, we found that the 123-model prediction is consistent with the measured mWCDF at a 95% Confidence Level (CL).